2016
DOI: 10.1038/ncomms12251
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale observation of oxygen delivery during silver–oxygen nanoparticle catalysed oxidation of carbon nanotubes

Abstract: To probe the nature of metal-catalysed processes and to design better metal-based catalysts, atomic scale understanding of catalytic processes is highly desirable. Here we use aberration-corrected environmental transmission electron microscopy to investigate the atomic scale processes of silver-based nanoparticles, which catalyse the oxidation of multi-wall carbon nanotubes. A direct semi-quantitative estimate of the oxidized carbon atoms by silver-based nanoparticles is achieved. A mechanism similar to the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…24) Note that it has been previously pointed out that the oxygen solute atoms in Ag cause changes in the lattice constant. 25,26) Since the lattice constant of the Ag nanoparticles measured by XRD agrees with the reported value, it is concluded that the amount of solute oxygen in the nanoparticles was negligibly small. In addition, the WDS analysis results show that the oxygen content in the Ag nanoparticles was below the detection limit (100 ppm), and no Ag oxides were found by FE-SEM.…”
Section: Resultssupporting
confidence: 83%
“…24) Note that it has been previously pointed out that the oxygen solute atoms in Ag cause changes in the lattice constant. 25,26) Since the lattice constant of the Ag nanoparticles measured by XRD agrees with the reported value, it is concluded that the amount of solute oxygen in the nanoparticles was negligibly small. In addition, the WDS analysis results show that the oxygen content in the Ag nanoparticles was below the detection limit (100 ppm), and no Ag oxides were found by FE-SEM.…”
Section: Resultssupporting
confidence: 83%
“…Fortunately, the advent of modern in situ high-resolution transmission electron microscopy (HRTEM), combined with image processing technique, enables probing the mechanism behind complicated physicochemical processes at the atomic scale. For example, nowadays novel phase formation 30 , 31 and transition 32 , 33 , metal-catalyzed process 34 , deformation twinning generation 35 , irradiation-induced void formation 36 as well as nanocrystal facet development 37 have been captured in real-time observations.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic-level observation and atomistic simulations/calculations are desirable to clarify these scientific phenomena. To resolve atomic-scale dynamic hydrogenation process, in-situ environmental transmission electron microscopy (ETEM) that has evolved dramatically in recent years offers the capability for temperature-, time-, and pressure-resolved imaging of gas–surface reactions by introducing a reactive gas to the sample while simultaneously monitoring the structural evolution. Theoretical calculations using first-principles density function theory (DFT) provides other evidence to elucidate these processes …”
Section: Introductionmentioning
confidence: 99%